HUBUNGAN TINGKAT PENGETAHUAN DAN KOMUNIKASI TERAPEUTIK PERAWAT TERHADAP TINGKAT KECEMASAN PASIEN HIPERTENSI DI RUANG INTERNA RSD DR. H. MOH. ANWAR SUMENEP - Cory Nelia Damayanti; Zakiyah Yasin (Fakultas Ilmu Kesehatan, 2011)
Communication of therapeutic represent one of the supporter factor in service of treatment, because ability communicate will water down gift giving of aid to good patient of medical service and also non is medical. According to Elbert dkk, 1964 intervention pursuant to communication can lessen dread, feel pain bone, usage of analgesia at patient.Research design performed within research if evaluated from data analysis or presentation of data of is including analytic research because got tobe data to be including research of cross sectional and evaluated from nature of its problem is incluiding type research of correlation. Amount of responden 15 people. Sample pylled from population by accidental sampling. Intake of data conducted with sheet of questioner and observation. Result analysis indicate that there are relation among communication of therapeutic nurse to story: evil dread of hypertension patient. As according to analysis got by meaning number of p = 0,00 its meaning there is relation which is significant access its meaning r = 1 chorelas confession degree of strength of relation among therapeutic to story: evil dread patient is very strong.Node able tobe by is excelsior mount knowledge of nurse about communications of therapeutic, will be good also communications of therapeutic used. While communication of therapeutic good among patient and nurse can give psychologiocal impact to patient which slowly that dread lose and turn into motivation to patient tobe able to immediately recover.Keyword : Story level knowledge of nurse, Communications therapeutic and story level dread of patient.